The Impact of Using Audio Aids by Teachers at Secondary Schools to Improve Pupils' Speaking Skill (Comprehensive Journal of Science, 2026)
This study examines the effect of using audio aids by teachers in secondary schools in Azawia City. A mixed-methods approach was used to gather data,  a questionnaire completed by 23 teachers who employed audio materials, and semi-structured interviews with the participating students . The questionnaire Thematic analysis of interview data supported the finding that audio aids positively influenced secondary school classrooms. Although some challenges were noted, the benefits of incorporating audio materials were clear, particularly in improving students' speaking skills. Teachers highlighted the role of audio aids in boosting student engagement with the language. Overall, the findings demonstrate that the use of audio aids enhances learner performance, builds confidence, and improves English communication abilities. This study offers some recommendations and opening new doors for new researchers.
Keywords: Audio aids, speaking skills, listening skills, secondary.